2011
DOI: 10.1111/j.1365-2648.2011.05688.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication administration via enteral tubes: a survey of nurses’ practices

Abstract: Enteral medication administration practices are inconsistent. Some nurses are using unsafe practices and may therefore compromise patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 10 publications
0
64
0
10
Order By: Relevance
“…39 Our results are in agreement with other studies that reported auscultation was used by 73% to 93% of critical care nurses to verify initial feeding tube placement. 2,40,41 Of the practices examined in our survey, auscultation required the least amount of specialized equipment or supplies, which may be one of the reasons this practice continues to be widely used. 2 It is disconcerting that auscultation continues to be one of the most commonly used methods for feeding tube verification.…”
Section: Discussionmentioning
confidence: 99%
“…39 Our results are in agreement with other studies that reported auscultation was used by 73% to 93% of critical care nurses to verify initial feeding tube placement. 2,40,41 Of the practices examined in our survey, auscultation required the least amount of specialized equipment or supplies, which may be one of the reasons this practice continues to be widely used. 2 It is disconcerting that auscultation continues to be one of the most commonly used methods for feeding tube verification.…”
Section: Discussionmentioning
confidence: 99%
“…Pese a lo anterior, en nuestro estudio, al igual que en otros, el personal en su mayoría conoce los fármacos más adecuados que deben administrarse por sonda 5,17 , así como el momento en el que deben lavar la sonda al administrar un medicamento 18 , sin embargo, no fue suficiente para obtener un conocimiento adecuado, puesto que los errores muestran falta de conocimiento y desempeño en la práctica.…”
Section: Resultsunclassified
“…According to Phillips and Endacott (2011), one third of nurses studied stated that enteric-coated medication could be administered when no other form was available, revealing that nurses have insufficient knowledge about the safety risks associated with destroying the enteric coating (Lohmann et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, errors related to this route of administration happen more often than reported or recognized (Institute for Safe Medication Practice, 2010). The issues raised are pertinent across countries (Phillips and Endacott, 2011), but there is a knowledge gap regarding the safe handling of feeding tubes especially in developing healthcare institutions. Studies that aim to identify evidence-based interventions targeting safe oral medication preparation and administration through feeding tubes can reduce that gap and the risks of complications, and decrease the overall costs of care.…”
Section: Introductionmentioning
confidence: 99%